Fantappstic : mobile location reminder application / Siti Khadijah Erni Azwadi - Erni Azwadi, Siti Khadijah (2022)
The demand for mobile phones is growing day by day. In today's world, the purpose of using a smart-phone is to gain access to additional services especially location-based reminder. A location reminder apps requires GPS systems to manage the current location of the user as part of its core purpose of alerting the user. Current location-based alarm applications are unable to provide information on a user 's exact direction to another selected spot of destination and the majority of the programmes were not user pleasant. To address this issue, this research paper attempted to create an application that allows users to mark locations where they should receive reminders. Location-based reminder also makes some individuals less likely to miss their destinations when travelling. In addition, users may plan time alarms by selecting a day and time. It features a straightforward design, as well as an easy to-use interface and environment. The primary goal of this research is to develop applications based on a time and location reminder software system, that will require the presence of some useful modules. This paper's technique is organized into five major phases: planning and analysis; design; implementation; testing; and evaluation. This research paper’s goal here is to help people with a good location reminder application. In the Fantappstic application, when the user generates the reminder, they will receive a notification if they are close to the location for which the reminder is set. This is calculated using the user's geographic area. For example, users will get a notification if they are near the location where the reminder is set. The user receives a notification within 100m of the mark. After delivering the alert notification, the getActivity() method displays the notification. Users will be able to handle their tasks more simply with this application. The characteristics of this mobile application will allow users to participate more often in their everyday life activities. In a nutshell, "Fantappstic" is a technology that promotes convenience while reducing the stress on human memory.